Kolaborasi Lintas Sektoral dalam Penanggulangan Isu Gelandangan: Studi Kasus di Kecamatan Ciamis, Kabupaten Ciamis - Vina Dwi Yulianti; Dini Yuliani; Irfan Nursetiawan (JOURNAL SAINS STUDENT RESEARCH, 2025)
The multidimensional problem of homelessness in Ciamis Regency demands coordinated action from the Public Order Agency (Satpol PP), the Social Services Agency, and the Health Agency. This study analyzes the roles of cross-sector actors in this issue using Ansel and Gash's (2007) theory of collaboration, with four dimensions: Initial Conditions, Institutional Design, Facilitative Leadership, and Collaborative Processes. Using a qualitative case study approach, data was collected through interviews, observations, and documentation. Results are available, but partial and suboptimal. Initial understandings among actors vary. The institutional design remains poorly structured, with suboptimal formal coordination and disintegrated policies. Leadership from the Social Services Agency is crucial, but communication and prioritization remain challenges. The collaborative process is linear, lacking a sustainable and integrated program, and minimal joint evaluation. The study concludes that the institutional design needs to be strengthened through a permanent coordination forum, an increased leadership role for program integration, and improvements to the collaborative process to make it more integrated and sustainable. Recommendations include developing comprehensive policies, increasing budgets, and establishing a joint evaluation mechanism for more effective homelessness management.